THE CORRELATION BETWEEN ATTITUDE AND MOTIVATION WITH THE IMPLEMENTATION OF SBAR COMMUNICATION TECHNIQUE DONE BY EMERGENCY ROOM NURSES WHILE DOING PATIENT HANDOVER IN A PRIVATE HOSPITAL IN WEST REGION OF INDONESIA - Amanda Rut; Theyman Laowo; Martina Pakpahan; Martha Octaria (Nursing Current: Jurnal Keperawatan, 2019)
The effective communication increase is one of the seven goals of patient safety. The SBARcommunication technique is part of it. There are several factors that influence the application of SBAR communication namely; knowledge, attitude and motivation. According to the Joint Commission International (JCI) and the World Health Organization (WHO) of 25,000-30,000 cases of permanent disability in patients in Australia, 11% was due to communication failure. Based on interviews by researcher with head nurses on February 19, 2018, March 3, 2018, March 4, 2018 and March 6, 2018 with several nurses and also the head nurse, and in three observations conducted in March in a Private Hospital in West Region of Indonesian, it was found that nurses had not conducted SBAR communication technique in accordance with the SOP (Standard Operational Procedure). This study was conducted to analyze the factors associated with the implementation of SBAR communication technique while doing patient handover by emergency Room nurses in a Private Hospital in West Region of Indonesia. This study employed quantitative methodology with a cross-sectional research design. Sampling was done by total sampling technique to 12 nurses. Data collection was done using a questionnaire to measure variables of the attitudes and motivation of nurses and observation sheets to assess the implementation of SBAR communication technique by nurses. The results of bivariate analysis using Chi-Square showed that there was a correlation between the attitude of emergency nurses with the implementation of SBAR communication technique while doing patient handover (p value <0.05), but there was no correlation between the motivation of nurses with the implementation of SBAR communication technique while doing patient handover (p value> 0.05). As the Suggestions for the hospital, the results of the study can be used as a reference in the implementation of SBAR communication technique by improving positive attitude of nurses.